Відношення логічного наслідку в логіках монотонних предикатів тa логіках антитонних предикатів - Шкільняк, О.С. (Проблеми програмування, 2017)
Досліджено відношення логічного наслідку в чистих першопорядкових композиційно-номінативних логіках часткових однозначних та часткових неоднозначних квазіарних предикатів. Описано відношення неспростовнісного, істиннісного, хибнісного та сильного логічного наслідку в логіках монотонних предикатів і логіках антитонних предикатів. Наведено приклади, які засвідчують відмінності одних відношень від інших, та встановлено співвідношення між різними відношеннями логічного наслідку. Исследованы отношения логического следствия в чистых первопорядковых композиционно-номинативных логиках частичных однозначных и частичных неоднозначных квазиарных предикатов. Описаны композиционные предикатные алгебры, языки и классы интерпретаций (семантики) этих логик, выделен ряд отношений логического следствия. Основное внимание акцентировано на изучении таких отношений в логиках монотонных предикатов и логиках антитонных предикатов. Для этих логик определено 20 отношений логического следствия, установлено, что из них лишь 7 раз-личных: PE |= IR , PE |= T , PE |= F , PE |= TF , RM |= T , RM |= F , RM |= TF . Приведены примеры, свидетельствующие о различии рассмотренных отношений логического следствия, установлены соотношения между такими отношениями. Logical consequence is one of the fundamental concepts in logic. In this paper we study logical consequence relations for program-oriented logical formalisms: pure first-order composition nominative logics of quasiary predicates. In our research we are giving special attention to different types of logical consequence relations in various semantics of logics of monotone predicates and logics of antitone predicates. For pure first-order logics of quasiary predicates we specify composition algebras of predicates, languages, interpretation classes (sematics) and logical consequence relations. We obtain the pairwise distinct relations: irrefutability consequence P |= IR , consequence on truth P |= T , consequence on falsity P |= F, strong consequence P |= TF in P-sеmantics of partial singlevalued predicates and strong consequence R |= TF in R-sеmantics of partial multi-valued predicates. Of the total of 20 of defined logical consequence relations in logics of monotone predicates and of antitone predicates, the following ones are pairwise distinct: PE |= IR, PE |= T, PE |= F, PE |= TF, RM |= T, RM |= F, RM |= TF. A number of examples showing the differences between various types of logical consequence relations is given. We summarize the results concerning the existence of a particular logical consequence relation for certain sets of formulas in a table and determine interrelations between different types of logical consequence relations.